STUDY OF OPTIMALIZATION SOLID WASTE OF REFUSE DERIVES FUEL (RDF) AT LANDFILL GRIYO MULYO, SIDOARJO DISTRICT - Putu Chandra Mandala; I.D.A.A Warmadewanthi; Ria Aniza (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2024)
Sidoarjo Regency in East Java grapples with a waste crisis, producing 1,086 tons/day in 2022, escalating annually due to urbanization. In response, Griyo Mulyo Landfill adopts Refuse Derived Fuel (RDF) technology, transforming waste into pellets for sustainable energy. This comprehensive waste management strategy not only addresses the increasing waste generation but also contributes to sustainable energy production, aligning with environmental and energy efficiency goals for the district. Aims: This study was aimed to assess the potential for waste reduction using Refuse Derived Fuel (RDF) technology in Sidoarjo Regency, East Java. Methodology and results: the focus of this study was on implementing RDF to convert waste into pellets, thereby reducing landfill reliance and transforming waste into a renewable energy source. The study involved analyzing the composition of waste entering the Griyo Mulyo Landfill Sidoarjo, revealing a significant portion of biodegradable, plastic, paper, and other materials. By determining the optimal RDF composition and estimating calorific values, the research aimed to provide insights into effective waste management strategies. Conclusion, significance and impact study: Analyzing the waste composition entering the landfill revealed optimal RDF components, emphasizing the potential for waste reduction and renewable energy production. The proposed inclusion of EM4 bioactivators in biodrying at Griyo Mulyo landfill promises accelerated decomposition, enhancing overall waste management efficiency. Significantly, this research offers practical insights for sustainable waste management in rapidly urbanizing regions, providing policymakers, waste authorities, and environmentalists with valuable strategies to mitigate the environmental impact of increasing urbanization. The potential impact extends to cleaner energy sources and influences waste management policies, fostering eco-friendly practices in Sidoarjo and beyond.